Surgical timing after preoperative chemotherapy is associated with oncologic outcomes in resectable colorectal liver metastases. Issue 8 (25th February 2022) - Sutton, Thomas L.; Wong, Liam H.; Walker, Brett S.; Dewey, Elizabeth N.; Eil, Robert L.; Ibewuike, Uchechukwu; Chen, Emerson Y.; Rocha, Flavio G.; Billingsley, Kevin G.; Mayo, Skye C.
Abstract: Introduction: Preoperative chemotherapy (POC) is often employed for patients with resectable colorectal liver metastasis (CRLM). The time to resection (TTR) following the end of chemotherapy may impact oncologic outcomes; this phenomenon has not been studied in CRLM. Methods: We queried our institutional cancer database for patients with resected CRLM after POC from 2003 to 2019. TTR was calculated from date of last cytotoxic chemotherapy. Kaplan–Meier analysis and multivariable Cox proportional hazards modeling were used to analyze recurrence‐free survival (RFS) and overall survival (OS). Results: We identified n = 187 patients. One hundred twenty‐four (66%) patients had a TTR of <2 months, while 63 (33%) had a TTR of ≥2 months. Median follow‐up was 36 months. On Kaplan–Meier analysis, patients with TTR ≥ 2 months had shorter RFS (median 11 vs. 17 months, p = 0.002) and OS (median 44 vs. 62 months, p < 0.001). On multivariable analysis, TTR ≥ 2 months was independently associated with worse RFS (hazard ratio [HR] = 1.54, 95% confidence interval [CI] = 1.06–2.22, p = 0.02 ) and OS (HR = 1.75, 95% CI = 1.11–2.77, p = 0.01). Conclusion: TTR ≥ 2 months following POC is independently associated with worse oncologic outcomes in patients with resectable CRLM. We therefore recommend consideration for hepatic resection of CRLM within this window whenever feasible.